A Comparison of Aerobic Bacterial Culture between BAL and Induced Sputum Method on HIV-AIDS Patient with Bacterial Pneumonia CO-Infection - Isnin Anang Marhana; Amir Sholeh (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2019)
Background: Bacterial pneumonia is the main cause of morbidity and mortality in immunocompromised individuals. The incidence of bacterial pneumonia on HIV patients is 2,3 cases per 100 people per year. On several cases, obtaining sputum sample for cultivation to confirm bacterial pneumonia diagnosis is difficult, thus further work to gain representative sample is necessary. This can be acquired through sputum induction and bronchoscopy. This study aims to compare aerobic bacteria culture result between BAL and induced sputum NaCl 3% method. Method: This is a comparative analytical study which was done in UPIPI dr. Soetomo Hospital Surabaya on HIV-positive patients between 21 – 60 years old with suspected bacterial pneumonia through clinical and radiology findings. All patients went through sputum induction and BAL procedure. The sputum obtained was cultured aerobically to confirm the diagnosis of bacterial pneumonia. Results: There were 26 subjects with average age 40 years old and male majority (73,1%). All patients were present with coughing and breahtlessness as their chief complaint, while the general complaint was coughing with difficulty in excreting sputum. The dominant risk factor is a history of free sex. The radiologic findings were dominated with unilateral infiltrate (73,1%). Most of the FOB imaging results were normal (88,5%). The results of aerobic bacterial culture from sputum induction are: Streptococcus pneumoniae (20%), Pseudomonas aeroginosa (20%), Acinetobacter spp. (20%), while from BAL method: Klebsiella pneumoniae (25%). The different specimen-obtaining method between induced sputum and BAL method has significant result with p= 0,001 (p